Dystocia due to Incomplete Cervical Dilatation in Goat and its Non-Surgical Management - Sharma, Renu; Gupta, Shashikant; Yadav, Brijesh Kumar; Das, Goutam Kumar; Jinagal , Sujata (The Indian Journal of Animal Reproduction, 2023)
A four-year-old non-descript doe in her third parity was presented to Referral Veterinary Polyclinic, ICAR-IVRI with a clinical history of failure to deliver kid even after completion of the gestation period. The doe was showing intermittent straining since 24 hours and visual examination could not detect any genital discharge from the vulva. Per-vaginal examination revealed one finger dilatation (external os) indicating that the dystocia was due to insufficient cervical dilation. The induction treatment was advised along with CMC massaging of cervix for 10 minutes at every 30 minutes interval. After 2 hours following therapy, the cervix was fully dilated and first water bag appeared at vulva. Per-vaginal delivery was performed with gentle traction yielding two live fetuses. The doe was recovered uneventfully and treatment with antibiotics and supportive therapy was advised for three days.
Keywords: Dystocia; Goat; Incomplete Cervical Dilatation; Management